"Building for the age" according to the principles of holism, individuality, and development: Historicism and architecture - Mađanović Milica (Filozofija i Društvo, 2022)
Originating from the fields of philosophy and history, the term historicism is often used by architectural historians. Aiming to contribute to the theoretical framework for the analysis of architectural historicism, the paper first explores the meaning of the concept in its native field of philosophy of history. The paper is aligned with the recent scholarship which interprets historicism as a worldview and deduces three historicist principles - principles of holism, individuality, and development. This paper argues that an historicist outlook marked wider creative achievements of an epoch, and that architecture of the period approximately ranging from the 1750s to the 1950s did not evade its influence. Finally, the paper illustrates the three principles in the idea of building for the age which haunted architects of the Western civilisation for almost two centuries.